STRENGTHENING ELEMENTARY SCHOOL EDUCATION CHARACTER WITH LOCAL WISDOM - Siti Humairoh (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
As time progresses with the rapid development of science and technology, it encourages people to always develop in various sectors or fields, including the education sector. Students from kindergarten to tertiary institutions are increasingly familiar with the development of science and technology to support the learning process. Students easily find information via the internet, both domestic and foreign information. The purpose of this research is to find out the strengthening of elementary school character education with local wisdom. The research method used is quantitative research. Quantitative research is a type of research that basically uses a deductive-deductive approach. Character education as one of the most important aspects in creating quality human resources. Teachers must instill character education from basic education, so that students have a strong foundation in social life. Strengthening character education through local wisdom needs to be done by teachers so that students are increasingly familiar with the local environment and are increasingly in love with the culture of their own people.